MENYOAL KOMUNITAS PUNK DI ACEH DALAM PERSPEKTIF DIFFERENTIAL ASSOCIATION - Cut Irna Liyana (Jurnal Community, 2015)
In recent years, Punk widely reported presence in Aceh. The existence of this community is predicted disturbing the lives of people in Aceh. So it becomes a problem that must be dealt with thoroughly. Therefore, this paper examines and describes the punk community as one form of social deviation in the differential perspective association. As of studies conducted, resulting that punk was present in Aceh today is the result of interaction with foreign cultures (other cultures). it can be proven by further examining the activities and behavior of teenagers who called himself punker, much of Aceh culture is loaded with Islamic law. Efforts to do to overcome this community, namely: providing guidance; developing policies that focus on social issues, improving the education system, increasing social control and control of the family.